New Headway. Advanced: Student's book - Soars L. Liz (New York, Oxford University Press, 2010)
The world's most trusted English courseNew Headway is the course teachers and learners can rely on. Why? An authoritative integrated syllabus, motivating topics, and clearly focused tasks combine with a real understanding of what works in the classroom. It all makes for effective teaching and effective learning.Tried and tested all over the world, it's probably the most popular course ever written! What's in New Headway Advanced? Up-to-date international topics stimulate interest and discussion. A focus on lexis and spoken language in a challenging language syllabus. Streamlined structure and design for maximum clarity and sense of progress.